New approaches to virgin olive oil quality, technology, and by‐products valorization. Issue 11 (November 2015) - Servili, Maurizio; Esposto, Sonia; Taticchi, Agnese; Urbani, Stefania; Di Maio, Ilona; Veneziani, Gianluca; Selvaggini, Roberto
Abstract : Extra virgin olive oil (EVOO) merchandize quality is based on analytical parameters describing alteration status and assuring genuineness, but qualitative/quantitative composition of those quality markers related to health and sensory aspects such as monounsaturated fatty acids, phenolic compounds as secoiridoid derivatives, and C5 and C6 volatile compounds are not mentioned. This paper focuses on the new approaches to the definition of EVOO quality that might include also healthy and sensory parameters and on the agronomic and technological factors that most influence their variability. Crushing and malaxation are discussed as critical points of the technological process since their direct involvement on the phenolic release and on the aroma generation. Variables such as time, temperature, and oxygen level, during malaxation, were analyzed to design new implant systems for the improvement of EVOO quality. Flash thermal conditioning (FTC) of the crushed olive pastes was briefly discussed as a new approach to the technological process. The rapid reaching of the optimal malaxing temperature seems to improve polyphenols and volatile concentration. The paper shows also recent studies on the valorization of the mechanical extraction co‐products as stoned pomaces for the animal feeding and vegetation waters phenolic concentrates and extracts for functional foods and ingredients production. This article provides an overview of the Author keynote lecture delivered at the Euro Fed Lipid Congress and focuses on the group's works. The GA report, shows the new approach to the EVOO technological process through the use of the flash thermal conditioning (FTC) of the crushed olive pastes to improve EVOO quality and the results obtained in terms of by‐products valorization showing the new applications of pomaces as animal feed supplement and the recovery of the crude phenolic concentrate (CPC) from olive vegetation water that could be used for functional food and ingredients production. Abstract : The GA report, shows the new approach to the EVOO technological process through the use of the flash thermal conditioning (FTC) of the crushed olive pastes to improve EVOO quality and the results obtained in terms of by‐products valorization showing the new applications of pomaces as animal feed supplement and the recovery of the crude phenolic concentrate (CPC) from olive vegetation water that could be used for functional food and ingredients production.